Environmental, Social and Governance and Creditworthiness: Two Contrary Evidence from Major Asian Markets - Narapong Srivisal; Natthawat Jamprasert; Jananya Sthienchoak; Pornpitchaya Kuwalairat (Asian Academy of Management Journal of Accounting and Finance, 2021)
Assets managed under sustainable investment criteria have been massively growing during the recent years. Among the criteria, environmental, social and governance (ESG) score leads the group as an important indicator of non-financial quality of a firm, which may reflect value to investors either through higher expected profit or lower risk. In this paper, we focus on the latter by exploring whether ESG score has linkage to the credit rating of firms due to the risk mitigation effect. Ordered logistic regressions are applied on a panel dataset of listed companies in Shanghai Stock Exchange and Tokyo Stock Exchange from 2009 to 2018. The results suggest that only in Japan, having ESG coverage is greatly associated with being awarded higher credit rating. However, only the environmental and governance pillars positively link to the Japanese firms’ credit ratings, while the social pillar shows negative correlation. The finding of heterogeneous effects translates to an important implication that investment in ESG should be taken with care as the impact of ESG may depend on different nature or culture of markets.